A Rare Occurrence of Primary Hepatic Leiomyosarcoma Associated with Epstein Barr Virus Infection in an AIDs Patient - Haritha Chelimilla; Kanthi Badipatla; Ariyo Ihimoyan; Masooma Niazi (Case Reports in Gastrointestinal Medicine)
Primary hepatic leiomyosarcoma is exceedingly rare accounting for less than 1% of the hepatic tumors. Close to 45 cases have been reported in the English literature. Presentation is usually nonspecific and diagnosis is often delayed until tumors reach a large size. This leads to a dismal prognosis. The tumors are not yet fully understood, hence the standard of care is not well defined. Curative resection remains the mainstay of management. Close association of Epstein Barr virus (EBV) induced soft tissue sarcomas is proven, especially in the presence of immunosuppression encountered in HIV/AIDS patients and in posttransplant patients. We herein present a case report of a 54-year-old man diagnosed to have HIV/AIDS and EBV infection admitted to our hospital with complaints of intractable hiccups for more than a week. Extensive workup revealed primary leiomyosarcoma of the liver.